European Regions and Boundaries A Conceptual History - Mishkova, Diana; Trencsényi, Balázs (Berghahn Books, 2017)
It is difficult to speak about Europe today without reference to its constitutive regions-supra-national geographical designations such as "Scandinavia," "Eastern Europe," and "the Balkans." Such formulations are so ubiquitous that they are frequently treated as empirical realities rather than a series of shifting, overlapping, and historically constructed concepts. This volume is the first to provide a synthetic account of these concepts and the historical and intellectual contexts in which they emerged. Bringing together prominent international scholars from across multiple disciplines, it systematically and comprehensively explores how such "meso-regions" have been conceptualized throughout modern European history.